2016
DOI: 10.1902/jop.2015.150246
|View full text |Cite
|
Sign up to set email alerts
|

Ridge Preservation After Tooth Extraction With Buccal Bone Plate Deficiency Using Tunnel Structured β‐Tricalcium Phosphate Blocks: A 2‐Month Histologic Pilot Study in Beagle Dogs

Abstract: Tunnel β-TCP blocks represent an effective bone-graft material for alveolar ridge preservation in fresh extraction sockets with buccal bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…ARP aims to minimize external resorption of the ridge and to maximize bone formation within the socket. Various techniques have been described in literature, frequently varying greatly in difficulty and biomaterials used (Jung et al 2013, Barone et al 2015c, Canullo et al 2015, Ikawa et al 2015, Lee et al 2015, Mendoza-Azpur et al 2015, Sbordone et al 2015. The use of autologous bone particles did not significantly alter the ridge resorptive process (Ara ujo & Lindhe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ARP aims to minimize external resorption of the ridge and to maximize bone formation within the socket. Various techniques have been described in literature, frequently varying greatly in difficulty and biomaterials used (Jung et al 2013, Barone et al 2015c, Canullo et al 2015, Ikawa et al 2015, Lee et al 2015, Mendoza-Azpur et al 2015, Sbordone et al 2015. The use of autologous bone particles did not significantly alter the ridge resorptive process (Ara ujo & Lindhe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Placement of biomaterials into jeopardized extraction sockets has been shown to reduce the degree of the ridge alterations and prevent soft tissue ingrowth (Ikawa et al, ; Lee, Jung, et al, ; Takahashi, Marukawa, & Omura, ). The application of barrier membranes has further been suggested to prevent soft tissue invasion endeavored especially when there is the absence of the buccal bony wall (Darby, Chen, & Buser, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine hydrochloride (2% with 1:80,000 epinephrine) was administered as a local anesthetic. Experimental defects were prepared as described in a previous study . In each dog, an intracrevicular incision was made from the maxillary canine to the second premolar, and a mucoperiosteal flap was elevated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this resorptive process often results in a more lingually relocated alveolar ridge . In beagle dogs, it has been shown that pronounced dimensional remodeling occurs at extraction sockets with buccal bone deficiency when graft materials are not used . Various alveolar ridge preservation techniques following tooth extractions have been developed to date .…”
Section: Introductionmentioning
confidence: 99%